Bahasa Inggris - runik machfiroh; Ulfa Nafi’ah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
Boredom among students at Islamic Boarding Schools is a persisting issue, particularly in non-academic programs, and has yet to be resolved. This study aims to analyze the extent of the impact of the innovation results of the 'Morserians!' board game in addressing student boredom in non-academic programs at SMAIT As-Syifa Boarding School. The method used is a mixed-method with a design approach. The primary data collection technique through observation was conducted by the researcher directly observing the activities of students related to the research topic, providing an overview of the objects under study documented in the form of photos and notes. Structured interviews were conducted with foundation officials, teachers, and students, along with unstructured interviews and questionnaires for 11th-grade students at SMA As-Syifa with a population of 2000. The sampling technique, Nomograph Harry King, was employed, targeting 480 individuals. Secondary data was obtained through literature study. The results of this study indicate that the innovation of the 'Morserians!' board game has a positive impact on addressing student boredom in non-academic programs at SMAIT As-Syifa Boarding School. There is an increase in engagement scores for male students by 17.1% and for female students by 44.8%. The 'Morserians!' board game emerges as an innovative educational media for non-academic programs, particularly in the Scout program, which can be utilized to enhance student learning motivation.